A Silkworm Infection Model for In Vivo Study of Glycopeptide Antibiotics - Aurora Montali; Francesca Berini; Maurizio Francesco Brivio; Maristella Mastore; Alessio Saviane; Silvia Cappellozza; Flavia Marinelli; Gianluca Tettamanti (MDPI AG, 2020)
Glycopeptide antibiotics (GPAs) are drugs of last resort for treating infections by Gram-positive bacteria. They inhibit bacterial cell wall assembly by binding to the d-Ala-d-Ala terminus of peptidoglycan precursors, leading to cell lysis. Vancomycin and teicoplanin are first generation GPAs, while dalbavancin is one of the few, recently approved, second generation GPAs. In this paper, we developed an in vivo insect model to compare, for the first time, the efficacy of these three GPAs in curing Staphylococcus aureus infection. Differently from previous reports, Bombyx mori larvae were reared at 37 °C, and the course of infection was monitored, following not only larval survival, but also bacterial load in the insect body, hemocyte activity, phenoloxidase activity, and antimicrobial peptide expression. We demonstrated that the injection of S. aureus into the hemolymph of B. mori larvae led to a marked reduction of their survival rate within 24-48 h. GPAs were not toxic to the larvae and cured S. aureus infection. Dalbavancin was more effective than first generation GPAs. Due to its great advantages (i.e., easy and safe handling, low rearing costs, low antibiotic amount needed for the tests, no restrictions imposed by ethical and regulatory issues), this silkworm infection model could be introduced in preclinical phases-prior to the use of mice-accelerating the discovery/development rate of novel GPAs.